Between Facticity and Hope: Heidegger, Benjamin, and Agamben in José Esteban Muñoz’s Queer Hermeneutics - Periañez Llorente, Luis (Anales del Seminario de Historia de la Filosofía, 2026)
This article traces the philosophical genealogy linking Heidegger, Benjamin, and Agamben to José Esteban Muñoz’s queer hermeneutics. Starting from Heidegger’s notion of facticity and Agamben’s paradigm of bare life, it examines how Muñoz reinterprets the ontology of impropriety in aesthetic and affective terms. His thought transforms exposure and abandonment into forms of potency and hope, locating in affect the site of a historical politics of persistence. Drawing on Benjamin, temporality is conceived as interruption and promise: the time of the “not-yet,” where queer and brown community embodies an immanent utopia –an ontology of affect open to the future.